2019
DOI: 10.1038/s41598-018-38262-3
|View full text |Cite
|
Sign up to set email alerts
|

Presaccadic attention improves or impairs performance by enhancing sensitivity to higher spatial frequencies

Abstract: Right before we move our eyes, visual performance and neural responses for the saccade target are enhanced. This effect, presaccadic attention, is considered to prioritize the saccade target and to enhance behavioral performance for the saccade target. Recent evidence has shown that presaccadic attention modulates the processing of feature information. Hitherto, it remains unknown whether presaccadic modulations on feature information are flexible, to improve performance for the task at hand, or automatic, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 47 publications
6
64
0
Order By: Relevance
“…One interesting exception was the result that high SFs were more reliably identified during saccades than during fixation when the blanking period was introduced in Experiment 2. We speculate that this result is a consequence of well-established effects: During the preparation of a saccade, visuospatial attention selected the target of the movement Kowler, Anderson, Dosher, & Blaser, 1995;Ohl et al, 2017;Rolfs & Carrasco, 2012), increasing visual sensitivity for high SFs in an obligatory fashion (Li et al, 2016;Li, Pan, & Carrasco, 2019). In the context of our task, this increase in sensitivity at the saccade target could have led to two complementary phenomena.…”
Section: Distinct Motion Streaks Are Associated With High Task Performentioning
confidence: 68%
See 1 more Smart Citation
“…One interesting exception was the result that high SFs were more reliably identified during saccades than during fixation when the blanking period was introduced in Experiment 2. We speculate that this result is a consequence of well-established effects: During the preparation of a saccade, visuospatial attention selected the target of the movement Kowler, Anderson, Dosher, & Blaser, 1995;Ohl et al, 2017;Rolfs & Carrasco, 2012), increasing visual sensitivity for high SFs in an obligatory fashion (Li et al, 2016;Li, Pan, & Carrasco, 2019). In the context of our task, this increase in sensitivity at the saccade target could have led to two complementary phenomena.…”
Section: Distinct Motion Streaks Are Associated With High Task Performentioning
confidence: 68%
“…Yet, these jerky displacements are not part of our perceptual experience—the visual world is stable. Whereas this phenomenon has received attention for centuries and has inspired research and theory to this date ( Binda & Morrone, 2018 ; Burr & Morrone, 2011 ; Cavanagh, Hunt, Afraz, & Rolfs, 2010 ; Hall & Colby, 2011 ; Higgins & Rayner, 2015 ; Marino & Mazer, 2016 ; Wurtz, 2018 ; Ziesche & Hamker, 2014 ), a fundamental question remains unanswered: How does the visual system keep track of an object that is changing locations on the retina as the eyes move ( Rolfs, 2015 ; Wurtz, 2008 )? That is, how do we determine a correspondence between two successive views of an object across a saccade?…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using a neutral or invalid-cued baseline (Hanning et al, 2018; Jonikaitis & Deubel, 2011; Rolfs & Carrasco, 2012; Rolfs et al, 2013; White et al, 2013) have all showed enhancement relative to an invalid or neutral baseline. Recent studies have shown a saccade-related modulation at the target or on the surface containing the target that did not occur with mere covert attention (Ghahghaei & Verghese, 2017; Li, Barbot, & Carrasco, 2016; Li, Pan, & Carrasco, 2019). In contrast, Khan et al (2015) showed no saccade-related change at the target location relative to covert attention, although they found a saccade-related decline in sensitivity at distractor locations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that presaccadic attention enhances the gain and reduces the width of the orientation tuning for the saccade target (Li, Barbot, & Carrasco, 2016; Ohl, Kuper, & Rolfs, 2017). Moreover, it increases the gain to high SFs at the saccade landing position (Li et al, 2016), even when doing so is detrimental for the task (Li, Pan, & Carrasco, 2019). Given that presaccadic attention is deployed voluntarily in response to a central cue, it has been compared to endogenous attention (Li et al, 2016; Li, Pan, & Carrasco, 2019; Rolfs & Carrasco, 2012).…”
Section: Introductionmentioning
confidence: 99%